Systemic Dendrimer-Peptide Therapies for Wet Age-Related Macular Degeneration - Tony Wu; Chang Liu; Rangaramanujam M. Kannan (MDPI AG, 2023)
Wet age-related macular degeneration (AMD) is an end-stage event in a complex pathogenesis of macular degeneration, involving the abnormal growth of blood vessels at the retinal pigment epithelium driven by vascular endothelial growth factor (VEGF). Current therapies seek to interrupt VEGF signaling to halt the progress of neovascularization, but a significant patient population is not responsive. New treatment modalities such as integrin-binding peptides (risuteganib/Luminate/ALG-1001) are being explored to address this clinical need but these treatments necessitate the use of intravitreal injections (IVT), which carries risks of complications and restricts its availability in less-developed countries. Successful systemic delivery of peptide-based therapeutics must overcome obstacles such as degradation by proteinases in circulation and off-target binding. In this work, we present a novel dendrimer-integrin-binding peptide (D-ALG) synthesized with a noncleavable, "clickable" linker. In vitro, D-ALG protected the peptide payload from enzymatic degradation for up to 1.5 h (~90% of the compound remained intact) in a high concentration of proteinase (2 mg/mL) whereas ~90% of free ALG-1001 was degraded in the same period. Further, dendrimer conjugation preserved the antiangiogenic activity of ALG-1001 in vitro with significant reductions in endothelial vessel network formation compared to untreated controls. In vivo, direct intravitreal injections of ALG-1001 and D-ALG produced reductions in the CNV lesion area but in systemically dosed animals, only D-ALG produced significant reductions of CNV lesion area at 14 days. Imaging data suggested that the difference in efficacy may be due to more D-ALG remaining in the target area than ALG-1001 after administration. The results presented here offer a clinically relevant route for peptide therapeutics by addressing the major obstacles that these therapies face in delivery.